Application of Phase-Only Correlation to Travel-Time Determination in GNSS-Acoustic Positioning - Honsho, Chie; Kido, Motoyuki; Ichikawa, Toshihito; Ohashi, Toru; Kawakami, Taichi; Fujimoto, Hiromi (Frontiers in Earth Science, 2021)
The GNSS-acoustic technique is a geodetic method for oceanic areas that combines GNSS positioning of a sea-surface platform and acoustic ranging of seafloor stations. Its positioning accuracy is typically a few and several centimeters for the horizontal and vertical positions, respectively. For further accuracy enhancement, we examined the errors in travel time, the most fundamental data in acoustic ranging. The reference signal used in our observations is a series of sinusoidal waves modulated by binary phase-shift keying with a maximal length sequence whose auto-correlation has a clear main peak at zero lag. However, cross-correlation between the actual returned signal and reference signal is often accompanied by many large sidelobes and looks very different from the synthetic auto-correlation. As a practical measure, we have chosen empirically one peak among several comparable peaks in the cross-correlation, though that is likely to lead to systematic errors in travel time. In this study, we revealed that a variety of cross-correlation waveform primarily depends on the incident angle of acoustic paths and that sidelobes were significantly reduced by substituting phase-only correlation (POC) for conventional cross-correlation. We therefore developed a template-matching technique using POC for the peak detection. POC templates were prepared by stacking actual POCs with certain ranges of the incident angle for each campaign. In the application of this method to actual data, we achieved successful results of our numerous campaign data to date. We consider that POC is advantageous in identifying the main peak uniquely and performing template matching more robustly, because POC enhances short-period components and thus highlights the timing of phase changes further than conventional cross-correlation.